Contributions of physical education teachers’ competences to students’ learning achievements - M. Hamid Anwar; Hari Amirullah Rachman; Joko Purwanto; Sudardiyono Sudardiyono (Jurnal Keolahragaan, 2020)
This study aims to determine whether the competences of Physical Education (PE) teachers make contributions to the quality of learning achievements of elementary school students. It was qualitative descriptive research using a reflective explorative approach. The subject of this study was the result of competence test of PE teachers in Yogyakarta Special Region in 2016. The study involved 60 PE teachers who were subjected to have an FGD (Forum Group Discussion) in some stages. The results show that the average score obtained by elementary school PE teachers in their Teacher Competence Test (TCT) stage II in 2016 was 61.79 for the pedagogical competences, and 60.07 for the professional competences. These results could exceed the national average score of 53.7. Based on the interviews with several teachers, the results of the competence tests had not indicated that PE elementary school teachers could improve the students’ learning quality. The teachers focused more on their preparations to take the TCT as a part of the assignments to the Learning Teacher program they participated in. This study also reveals that the TCT scores did not make a significant contribution to the students’ learning achievements in PE subject. Furthermore, TCT was considered by the teachers as a goal and not as an instrument to improve their competences in the teaching and learning processes.